Integration Of Marketing 5.0 Strategy And Digital Ethics To Improve Customer Loyalty In The Era Digital Transformation - Royda Sagala; Danyel Julfan Sinaga; Rofan Aceh; Dandy Tambunan (PT. Padang Tekno Corp, 2026)
Digital transformation has significantly changed the marketing landscape, creating a need for strategies that integrate advanced technology with humanistic approaches and digital ethics. This study examines the integration of Marketing 5.0 strategies with digital ethical principles to enhance customer loyalty in today’s digital era. Based on a literature review from various recent books and journals, the research highlights the crucial role of big data, artificial intelligence (AI), augmented reality (AR), as well as marketing personalization and humanization in delivering relevant and meaningful customer experiences. Moreover, ethical aspects such as transparency, data privacy, and customer trust form a fundamental basis for building sustainable loyalty. The findings indicate that implementing a synergy of innovative technology and strong ethical standards can strengthen customer engagement and trust, while preserving corporate reputation in a competitive digital marketplace. Practical implications for companies include exploiting responsive and adaptive data-driven marketing and reinforcing communication grounded in human values. This study contributes theoretically and practically to the development of modern marketing strategies that are technology-driven as well as human-centered with digital ethics.